PERANCANGAN KAWASAN PANTI ASUHAN ISLAMI TERPADU DI KUBU RAYA - Fitri, Tama Ratna; Irwin, Irwin; Pebriano, Valentinus (Program Studi Arsitektur Fakultas Teknik Universitas Tanjungpura, 2026)
Orphanage is a social institution that provides substitute care to fulfill the physical, mental, and social needs of children, particularly those who have lost their parents. Kubu Raya, one of the regencies in West Kalimantan Province, has a relatively large number of orphanages; however, most of them are inadequate in terms of facilities and supporting infrastructure. Moreover, Kubu Raya does not yet have an orphanage integrated eith educational facilities within a single complex that includes dormitories, schools, and a mosque. To address the needs of underprivileged children, especially orphans, it is essential to provide a proper facility that also incorporates religious education for its residents. The design objective of the Islamic Integrated Orphanaged Complex in Kubu Raya is to fulfill the needs of orphanaged residents in the learning process by implementing Islamic education through facilities and educational infrastructure managed by the Kubu Raya Government. This design is expected to serve as a supportive environment for underprivileged and orphaned children, enabling them to participate in educational activities while obtaining proper guidance within a safe, comfortable, and nurturing environment.This design employs the Richard Whitaker method, which consists of data collection, analysis, concept development, and preliminary design. The design outcome produces an area layout that includes dormitory buildings, a school, and a mosque.